2017
DOI: 10.22605/rrh4225
|View full text |Cite
|
Sign up to set email alerts
|

Speech–language pathology telehealth in rural and remote schools: the experience of school executive and therapy assistants

Abstract: Introduction: Difficulties in accessing allied health services, especially in rural and remote areas, appear to be driving the use of telehealth services to children in schools. The objectives of this study were to investigate the experiences and views of school executive staff and therapy assistants regarding the feasibility and acceptability of a speech-language pathology telehealth program for children attending schools in rural and remote New South Wales, Australia. The program, called Come N See, provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
(24 reference statements)
1
22
0
3
Order By: Relevance
“…13 Communication between all stakeholders was also recognised by school staff as essential for program success. 14 In our study, lack of communication regarding the program negatively influenced the satisfaction of some teachers. These findings highlight the importance of stakeholder engagement and clear communication when implementing such a program.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…13 Communication between all stakeholders was also recognised by school staff as essential for program success. 14 In our study, lack of communication regarding the program negatively influenced the satisfaction of some teachers. These findings highlight the importance of stakeholder engagement and clear communication when implementing such a program.…”
Section: Discussionmentioning
confidence: 63%
“…13 Another study showed a telehealth speech-language pathology program was acceptable to school executive and therapy assistants, but highlighted the need for a greater understanding of how to implement such programs. 14 Understanding the perceptions and experiences of school staff members is integral to ensuring program sustainability and determining scalability to other schools. This study aimed to explore the implementation requirements of a telehealth speechlanguage pathology program from the perspectives of staff at a rural Australian school.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst evidence exists on the importance of a clinical vision and purpose for telehealth and clinician and management ownership of these services (Bradford, Caffery, & Smith, 2016), limited evidence exists on: the role of communities in the codesign of these alternative services; service capacity to adapt to current and changing community needs; the depth of relationships between external service providers, local services and communities; and whether communities feel a sense of ownership and control of these services (Bywood, Raven, & Butler, 2013). Healthcare that lacks face-to-face interactions can be considered a second best option for rural and remote service recipients and providers (Bradford et al, 2016;Fairweather, Lincoln, & Ramsden, 2017). In the absence of face-to-face services, individuals, families and communities can feel obliged to accept healthcare alternatives despite preferring direct interactions and engagement with their healthcare providers (Bywood, Raven, & Butler, 2013).…”
Section: Slp Students In Rural and Remote Contextsmentioning
confidence: 99%
“…Contudo, há carência de estudos voltados para terapia das AFI via telessaúde, recurso que ainda não está totalmente estabelecido. Por essas razões, as informações ainda são incipientes em relação ao desempenho dos indivíduos à telessaúde, às abordagens terapêuticas e às metodologias tecnológicas utilizadas para viabilizá-las, uma vez que os estudos nessa temática ainda estão em desenvolvimento (Fairweather et al, 2017).…”
Section: Introductionunclassified